EFEKTIFITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA SIAK KOTA PEKANBARU - Eko Nurwahyanto; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Researcher indentify through mass media the indication of service to the community is not effective. Target of Local Water Company service in Pekanbaru City under the management of Regional Water Company Tirta Siak until now not improved, still many record of customer complaints service obtained Local Water Company Tirta Siak, Local Water Company Tirta Siak still depend on subsidy from Pekanbaru City budget. Research problem can be formulated as : why service of Local Water Company Tirta Siak is not effective? What’s factors influencing the effectiveness of Local Water Company Tirta Siak service? The purpose of this research is : To know about effective Local Water Company Tirta Siak the factors influencing the effectiveness of Tirta Siak Local Water Company service. Qualitative research method this research was conducted at Local Water Company Tirta Siak. Primary data source through interview and secondary. Data source technique of data analysis executed with descriptive qualitative.With indicators according to Zeithaml, Berry and Parasuraman are emphaty, there are still complaints from customers regarding the clean water service given about water quality and constancy. Direct indicator (tangible) has been fulfilled infrastructure facilities to support employee work and customers convenience. Reliability speed of employees in providing services and ease in the process of service procedures provided. Responsiveness, gresresponsiveness of Local Water Company Tirta Siak staff’s ability to handle customers complaints and provide services. Assurance of hospitality and courtesy of employees when providing services. Supporting factors: employees already have a high awareness of what to do. The existence of rules that bind employees in work. The existence of a clear division of tasks. Employee income is considered to be in accordance with the class and the period of work. Employees are skilled in their respective fields and able to do their job well. In addition Local Water Company Tirta Siak office is equipped with facilities that support the work of employees. Inhibiting factors: The season factor, during the dry season is very difficult to get water from the water source, the old pipe factor. Older pipe can lead to decreased quality, quantity and continuity of water.Keyword : Effectiveness, Service